FREQUENCY RATE OF VASCULAR DEMENTIA AND ITS RELATIONSHIP WITH TOPOGRAPHY AND ETIOLOGY IN STROKE PATIENTS - K Ghandehari (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Vascular dementia (VD) is a stroke complication which increases disability and dependency of the patients. This study was designed to evaluate the frequency rate of VD and its relationship with topography and etiology of stroke.METHODS: In this prospective study, consecutive ischemic stroke patients admitted in Valie-Asr hospital, Birjand, Iran, during 2006-2007. Diagnosis of ischemic stroke, its topography and etiology was made by neurologist based on the standard protocol. Ischemic VD was determined by DSMIV (diagnostic and statistical manual of mental disorders, fourth edition) criteria. Stroke etiology categorized as atherosclerotic, cardioembolic, miscellaneous, uncertain and mixed subtypes. VD was classified into cortical, subcortical and mixed subtypes.FINDINGS: Among 342 ischemic stroke patients, 21 patients (6.1%) had VD. Cortical, subcortical and mixed subtypes consisted 7, 7and 6 cases of VD topographies. VD was significantly more frequent in patients with simultaneous carotid and vertebrobasilar territories involvement, df=1, p<0.001. VD was found in 13.6% of patients with cardioembolic mechanism and 3.8% of other stroke patients which has a significant difference (df=1, p=0.001 OR=3.94).CONCLUSION: Vascular dementia is an infrequent complication of ischemic strokes. It is significantly more frequent in stroke patients with cardioembolic mechanism due to various territorial involvements.